In Silico Modeling for the Design of 2-substitted Benzimidazole Derivatives, and Prediction of Activity as Procaspase-3 Activators and Apoptosis Inducer - U. Kulkarni, Prajakta; D. Ghate, Manjunath; K. Vyas, Vivek (Letters in Drug Design & Discovery, 2017)
Background: Cancer is the leading cause of death worldwide. Induction of apoptosis in cancer cell is the main strategy for the development of anticancer agents targeting apoptosis pathway. Procaspase-3 is one such target for the induction of apoptosis via activation of caspase 3. Novel molecules are needed as procaspase-3 activators which will induce apoptosis in cancer cell. Objective: The main objective of this work is to design 2-substituted benzimidazole derivatives using 3D QSAR study, and to predict the activity of designed compounds as procaspase-3 activators, and apoptosis inducer. Method: 3D QSAR study was performed on the series of substituted benzothiazole derivatives using Sybyl X software. Distill alignment was used for 3D QSAR analysis. Best CoMFA and CoMSIA models were used for the activity prediction of designed compounds. External validation using MAE-based criteria were performed, and applicability domain of QSAR models were also determined. Osiris property explorer and Med Chem Designer software were used for the prediction of in silico pharmacokinetic properties, and toxicities. Results: CoMFA and CoMSIA models were developed using Distill alignment method, which were statistically very good, and validated using well known procedures. Contour maps generated using 3D QSAR study were used for the design of novel compounds. Designed compound showed better predicted activity, and no toxicity. Conclusion: The present QSAR approach with predicted activity and physicochemical properties helped in the design of benzimidazole derivatives as procaspase-3 activators and apoptosis inducer.
Keywords: benzimidazole derivatives